Beyond the information commons a field guide to evolving library services, technologies, and spaces - Forrest, Charles, 1953-; Halbert, Martin (Rowman & Littlefield, 2020)
"This new book updates this review of current practice in the Information Commons and other new kinds of facilities inspired by the same needs and intents. This book is an attempt to answer the question: "What might be the next emerging concept for a technology-enabled, user-responsive, mission-driven form of the academic library?""--